Stabilized carbon coating on microelectrodes for scalable and interoperable neurotransmitter sensing - Yongli Qi; Dongyeol Jang; Jaehyeon Ryu; Tianyu Bai; Yieljae Shin; Wen Gu; Aditya Iyer; Gen Li; Hongtao Ma; Jyun-you Liou; Matthijs van der Meer; Yi Qiang; et al. (Nature Communications)
Abstract Real-time monitoring of neurotransmitters is essential in driving basic neuroscience understandings and creating treatments for various brain disorders. However, current neurotransmitter sensing devices are highly limited in their spatiotemporal resolution and ability to integrate with neuronal recording. Here, we introduce a unique carbon coating approach to achieve high-performance voltammetry electrodes with extraordinary scalability and interoperability. Surprisingly, we discovered that mild annealing drastically improves the electrochemical stability of graphene-based carbon coating, enabling the transformation of conventional neuroelectrodes into fast-scan-cyclic-voltammetry-stable carbon sensors. We successfully validated sub-second detection of nanomolar dopamine in vivo using carbon-coated microelectrodes (CCMs) in rodents and demonstrated arrays of one hundred CCMs with high yield and uniformity. Furthermore, we developed a dual-modal neural probe that integrates the CCM with electrophysiological recording sites, allowing us to demonstrate that dopamine fluctuation in the ventral striatum of awake rats strongly correlates with the high gamma power in the brain with sub-second-level precision. Together, these advances pave the way for spatiotemporally scalable and multiplexed brain interfacing, with also broad applicability in electrochemical-related diagnostic and interventional approaches.